2016
DOI: 10.1017/jfm.2016.735
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of wavepackets in jets to nonlinear effects: the role of the critical layer

Abstract: Linear instability waves, or wavepackets, are key building blocks for the jet-noise problem. It has been shown in previous work that linear models correctly predict the evolution of axisymmetric wavepackets up to the end of the potential core of subsonic turbulent jets. Beyond this station, linear models fail, and nonlinearity is the likely missing piece. The essential underlying nonlinear mechanisms are unknown, and it remains unclear how these should be incorporated in a reduced-order model. The nonlinear in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 61 publications
5
53
0
Order By: Relevance
“…This is a typical manifestation of the Orr-mechanism and has similarly been observed in resolvent models of other flows (e.g. in Garnaud et al 2013;Dergham et al 2013;Jeun et al 2016;Semeraro et al 2016;Tissot et al 2017). The suboptimal modes in figure 6(d,f,h,j,l) contain two wavepackets: one in the initial shear layer region that is similar to the KH wavepackets in the optimal mode and a second further downstream in the developing jet region.…”
Section: Resolvent Spectra and Modessupporting
confidence: 72%
See 1 more Smart Citation
“…This is a typical manifestation of the Orr-mechanism and has similarly been observed in resolvent models of other flows (e.g. in Garnaud et al 2013;Dergham et al 2013;Jeun et al 2016;Semeraro et al 2016;Tissot et al 2017). The suboptimal modes in figure 6(d,f,h,j,l) contain two wavepackets: one in the initial shear layer region that is similar to the KH wavepackets in the optimal mode and a second further downstream in the developing jet region.…”
Section: Resolvent Spectra and Modessupporting
confidence: 72%
“…From a local stability theory point of view, the two mechanisms are distinguished by their modal and non-modal nature, see Jordan et al (2017) and Tissot et al (2017)). Tissot et al (2017) found that the critical layer, defined where the phase speed of the wavepacket is equal to the local mean velocity, plays an important role in the forced linear dynamics of jets. In accordance with our interpretation, their results suggests that the Orr-mechanism is active downstream of the potential core.…”
Section: Resolvent Spectra and Modesmentioning
confidence: 99%
“…IV B, these three POD modes can be understood as the highest-gain structures that arise in response to stochastic forcing by turbulence nonlinearities. We can add that, as shown by Tissot et al [23], the connection between the turbulent forcing and the high-gain structures occurs via the critical layer and involves an Orr-like mechanism affecting downstream fluctuations. The connection between these first few modes and the far field will be discussed in Sec.…”
Section: The Amplitude Envelopesupporting
confidence: 53%
“…Indeed, good agreement is only observed between the stability predictions and the second-order, single-point statistical moments upstream of the end of the potential core. In the downstream region, on the other hand, recent studies support the idea that wave packets persist here, but are forced by turbulence [23][24][25]. Despite the low levels of the forcing modes in this region, stabilization of the dominant convective instability leads to an accrued sensitivity to nonlinear effects that act predominantly via the critical layer.…”
mentioning
confidence: 66%
“…These reconstruction approaches rely on the ability of a mean flow stability model to accurately describe wavepackets, which has been studied in a substantial number of articles (Cavalieri et al 2013;Rodríguez et al 2015;Beneddine et al 2016;Tissot et al 2017). This large body of work shows that the use of such a model could be, in some situations, an interesting alternative to TR-PIV.…”
mentioning
confidence: 99%